Scaffolding creativity: Integrating problem-based learning with liveworksheets to enhance poetry writing skills in high school - Faridah Umi Hanifah; Miftakhul Huda (STAI Auliaurrasyidin Tembilahan, 2026)
Classroom observations in an eleventh-grade class at Muhammadiyah 1 Senior High School Sragen revealed low student engagement and limited poetry writing skills. To address this issue, this study examined the implementation of Problem-Based Learning (PBL) supported by Liveworksheets electronic student worksheets in poetry writing instruction. Using a descriptive qualitative case study design, data were collected through classroom observations, interviews with Indonesian language teachers, and questionnaires administered to 26 eleventh-grade students. The data were analyzed thematically following Braun and Clarke’s framework, with credibility ensured through data triangulation. The findings indicate improved student engagement, increased participation in learning tasks, and more positive perceptions of the learning process. Students also demonstrated greater involvement in collaborative dialogue during poetry writing activities. These results suggest that integrating interactive digital worksheets with problem-based learning can enhance student engagement and support the development of poetry writing skills at the senior secondary level.